Neural Correlates of Food Cue Exposure Intervention for Obesity: A Case-Series Approach - Franssen, Sieske; Jansen, Anita; Schyns, Ghislaine; van den Akker, Karolien; Roefs, Anne (Frontiers in Behavioral Neuroscience, 2020)
Abstract Background: People with overweight have stronger reactivity (e.g., subjective craving) to food cues than lean people, and this reactivity is positively associated with food intake. Cue reactivity is a learned response that can be reduced with food cue exposure therapy. Objectives: It was hypothesized that participants after food cue exposure therapy would show reduced neural activity in brain regions related to food cue reactivity and increased neural activity in brain regions related to inhibitory-control as compared to participants receiving a control lifestyle intervention. Method: Neural activity of ten women with overweight (BMI ≥ 27 kg/m2) in response to individually tailored visually presented palatable high-caloric food stimuli was examined before versus after a cue exposure intervention (n = 5) or a control lifestyle (n = 5) intervention. Data were analyzed case-by-case. Results: Neural responses to food stimuli were reduced in food-cue-reactivity-related brain regions after the lifestyle intervention in most participants, and generally not after the cue exposure therapy. Moreover, cue exposure did not lead to increased activity in inhibitory-control-related brain regions. However, decreased neural activity after cue exposure was found in most participants in the lateral occipital complex, which suggests a decreased visual salience of high-caloric food stimuli. Conclusions: Receiving a cue exposure therapy did not lead to expected neural responses. As cue exposure relies on inhibitory learning mechanisms, differences in contexts (e.g., environments and food types) between the intervention setting and the scanning sessions may explain the general lack of effect of cue-exposure on neural activity.